Problem-Based Learning Model Based on Predict-Observe-Explain (POE) to Improve IPAS Learning Outcomes - Bagus Bayu Budiarsa; I Made Sedana; I Nyoman Raka (Journal of Education Reseach and Evaluation, 2026)
This research is motivated by the low mathematics learning outcomes of elementary school students, which are influenced by the limited use of interactive learning media in the learning process. The implementation of science and science learning in elementary schools is still dominated by conventional teacher-centered methods, resulting in students being less actively involved in the scientific thinking process. This study aims to analyze the effectiveness of interactive media in improving mathematics learning outcomes of fifth-grade elementary school students. This study uses a quantitative, quasi-experimental, One-Group Pretest-Posttest design. The research subjects were 27 fifth-grade students selected using a total sampling technique. Data collection was conducted through mathematics achievement tests administered before and after the implementation of interactive media. The data were analyzed using descriptive and inferential statistics, including the Paired Sample t-Test, after satisfying the prerequisite tests for normality and homogeneity. The analysis showed a significant increase in students' mathematics learning outcomes after the treatment. This finding indicates a significant difference between students' pretest and posttest results. Thus, interactive media is effective in improving mathematics learning outcomes of elementary school students. This study provides implications for the use of interactive learning media in supporting the creation of more interesting, meaningful, and student-centered mathematics learning.